Çocuk resminde yakın çevre(9-12 yaş örneklerinde problemli aile ve okul) - Coşkun, Bahar (My University, 2003)
The aim in this production children who are between 9 -12 years how to effect on the pictures in their family with showing on their graphics arts. On the pictures which are concerned with closed relatives clearly show that there are some shape and content implicits that, they tell us child's feeling and manner. One the other hand it's too important for an educator to find out child's ability and to appraise it for child's benefit. While this object was prepared the children were chosen from families whose economical situations are lower than normally, in order to get realistic results. A lot of school were visited and had several important interview with many teachers and had masters, to reach the problem children. At last some of them had to draw pictures what they imagine. Besides, Kartal Guidance and Investigation Center visited and worked each other in order to reach more document for getting more realistic result. Social for the production of Children in Küçükyalı Nursery School was the main guide for our investigation with it's professional teachers and pedagogue. While the pictures were checking the knowledge forms about the children and his family filled under controlling from teachers and psychological guider with their valuable information also sometimes child's suggestions were used in these forms, too. The most interesting points in this production that prepared with over than hundred children are the thirty-three examples. In these thirty- three pictures children show their bad family connection, unhealthy feeding, troubled bed temper in living family atmosphere. Fractiousness each other their drawing pictures ( who has no parents ) show us that how important family's role on growth of a person with his psychological life.
Keywords: Çocuk Resimleri; Resim_Eğitim